O uso do tablet como recurso de apoio ao processo de ensino e aprendizagem: a percep????o de jovens e professores do ensino m??dio - Escalante, Simone Bordallo de Oliveira (2013)
The present study aimed at investigating the perception of first grade students in a private school in Brasilia, Distrito Federal - DF, on the use of the tablet in the development of their studies. It intended to analyze, from the point of view of young students, the challenges, the difficulties, and the conveniences of using the tablet in carrying out their activities in the classroom. This evaluation was conducted with 186 (one hundred eighty-six) young people aged between 14 and 17 years. Also participating in the research were fifteen (15) teachers, the Pedagogical Director of the school, and the teacher responsible for the project which inserted the tablet in the classroom activities. A qualitative and quantitative research was chosen, using the following techniques to collect data: questionnaires, focus groups, and semi-structured interviews. Given the results expressed therein, it was found that the tablet, from the perspective of students, was basically used as a digital book. The results showed that the use of the tablet may contribute to increased students??? performance, to the extent that the functions and available resources are exploited and used in the classroom, in order to set up a pedagogical resource in the teaching and learning process of young students along their school years.